Exploring the Relationship Between Maternal Circulating Hormones and Gestational Weight Gain in Women Without Obesity: A Cross-Sectional Study - Lappas M; Lim R; Price S; Prendergast LA; Proietto J; Ekinci EI; Sumithran P (Dove Medical Press, 2020)
Martha Lappas,1,2 Ratana Lim,1,2 Sarah Price,3,4 Luke A Prendergast,5 Joseph Proietto,3,4 Elif I Ekinci,3,4 Priya Sumithran3,4 1University of Melbourne, Department of Obstetrics and Gynaecology, Melbourne, Australia; 2Mercy Hospital for Women, Melbourne, Australia; 3University of Melbourne, Department of Medicine (Austin), Melbourne, Australia; 4Department of Endocrinology, Austin Health, Melbourne, Australia; 5La Trobe University, Department of Mathematics and Statistics, Bundoora, AustraliaCorrespondence: Priya SumithranUniversity of Melbourne, Department of Medicine (Austin), Repatriation Hospital, Level 1, Centaur Wing, 300 Waterdale Road, Heidelberg VIC, Melbourne 3081 AustraliaTel +61 3 9496 2375 Email priyas@unimelb.edu.auBackground: Central homeostatic regulation of fat stores is attenuated during pregnancy, to allow for adequate fat deposition to support fetal development and lactation. What factors particular to pregnancy facilitate fat accumulation, and why gestational weight gain (GWG) is so variable, are not clear. The aim of this cross-sectional study was to examine the associations between GWG and circulating hormones with known effects on appetite and growth.Methods: Women without obesity (body mass index, BMI < 30 kg/m2), with a healthy singleton pregnancy, were recruited at the time of delivery by elective Caesarean section at a tertiary obstetric hospital. Women with preterm (< 37 weeks) delivery and smokers were excluded. Maternal blood was collected at the time of delivery for measurement of fasting oestradiol, progesterone, prolactin, insulin, leptin, insulin-like growth factor 1 and insulin-like growth factor binding protein 3. Comparisons were made between women who gained weight within the range recommended by Institute of Medicine guidelines for normal weight women (11.5– 16 kg; n=34) and those who gained excessive weight (> 16 kg; n=35) during pregnancy. Analysis of covariance was carried out using multiple linear regression to test the effect of GWG group on biochemical parameters, accounting for pre-pregnancy BMI.Results: The 69 participants had a mean age of 34.6 ± 4.3 years, and pre-pregnancy BMI of (23.3 ± 1.8 kg/m2), with no significant differences between groups in pre-pregnancy weight, BMI, age, birthweight or parity. Mean GWG was 14.0 ± 1.3 kg in the “recommended” group and 19.6 ± 3.2 kg in the “excessive” group. Leptin was significantly higher (43.4 ± 21.6 vs 33.4 ± 15.0 ng/mL, p=0.03) and prolactin tended to be lower (159.5 ± 66.1 vs 194.0 ± 85.6 ng/mL, p=0.07) at delivery in women with excessive (vs recommended) GWG. No other circulating factors were found to differ between groups. The between-group difference in leptin remained after adjustment for pre-pregnancy BMI in multiple linear regression and quantile regression analyses.Conclusion: In women without obesity, leptin remains a marker of adiposity during pregnancy. GWG was not associated with other circulating hormones with effects on appetite and growth.Keywords: gestational weight gain, leptin, pregnancy, appetite